2012
DOI: 10.1177/0003319712459213
|View full text |Cite
|
Sign up to set email alerts
|

Coronary Artery Calcification Progression in Asymptomatic Individuals With Initial Score of Zero

Abstract: The aim of this study is to determine the progression of coronary artery calcification (CAC) using electron beam computed tomography (CT) when the initial CAC score (CACS) is zero and to determine the best interval to repeat a CAC scan. We studied 388 individuals with zero CACS (308 males; mean age: 48.8 ± 8.26 years) who underwent 2 consecutive CT scans in a period of at least 12 months apart. The interscan period was 2.99 ± 1.35 years (range: 1-6 years). Three-quarters of the individuals (75%) did not develo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
15
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 35 publications
1
15
1
Order By: Relevance
“…Similar results were seen in previous studies 2325 . The percentage of subjects who developed new CAC (36%) was higher in our study compared to previous studies 24, 25 , which is likely due to the older patient population, higher risk factor burden, and longer follow-up of subjects in our study. While a prior study by Min et al had the advantage of yearly CAC scanning, this study did not investigate the distribution of new CAC upon first detection 23 .…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Similar results were seen in previous studies 2325 . The percentage of subjects who developed new CAC (36%) was higher in our study compared to previous studies 24, 25 , which is likely due to the older patient population, higher risk factor burden, and longer follow-up of subjects in our study. While a prior study by Min et al had the advantage of yearly CAC scanning, this study did not investigate the distribution of new CAC upon first detection 23 .…”
Section: Discussionsupporting
confidence: 92%
“…In our study, 52% had CAC score of 1–10, 44% had CAC score of 11–100 and 4% had CAC score of >100. Our study has a higher burden of new onset CAC compared to the study by Gopal et al 30 (approximately 69% had CAC score of 1–9, 26% had CAC score of 10–50 and 5% had CAC score >50) and the burden is even less in the study by Koulaouzidis et al 25 (approximately 84% had CAC score of 1–9, 14% had CAC score of 10–50 and 2% had CAC score >50). Our study has an older patient population and higher traditional risk factor burden compared to prior studies, perhaps also explaining our observed burden of new onset CAC.…”
Section: Discussioncontrasting
confidence: 61%
See 2 more Smart Citations
“…15 In addition to surrogate monitoring of coronary plaque burden over time, a unique potential of serial CAC measurement is the ability to evaluate the success of risk factor modifications and medical treatment. 16 Electron-beam computed tomography has been shown to accurately assess the clinical efficacy of medical therapies in studies as short as 1 year. 17 This has the potential to allow primary care providers to tailor treatments for high-risk patients, such as those with known coronary disease, based on disease progression.…”
mentioning
confidence: 99%